ORDINASI SUNGAI BIRU DESA TULUNGREJO KECAMATAN BUMIAJI KOTA BATU BERDASARKAN MAKROZOOBENTHOS - Lorine Tantalu; Sri Sudaryanti; Mulyanto Mulyanto (Universitas Tribhuwana Tunggadewi, 2017)
This research aim to make ordination of Blue Rivers on Dusun Wonorejo, Desa Tulungrejo, Kecamatan Bumiaji, Kota Batu based on macrozoobenthos and environmental variable which support. The research is conducted in the early of February to mid of August. Items at the research consisting of macrozoobenthos community, water, environmental physical on Blur Rivers. Intake of some sample conducted in 15 sites which done only one intake as long as Blue River which representing reference site area. Way of intake of the makrozoobenthos sample are done with kicking sampling methods. Macrozoobenthos which had been taken would be identified and calculated as data sampling. Data analysis technique use CANOCO (“Canonical Community Ordination”) programs on 4.5 version for determining the ordination of ecology group based on makrozoobenthos. From data analysis use CANOCO to be got Blue River ordination from 15 sites that is A ordination counted 7 site that means are good condition proven by finding of Glossomatidae. B rdination counted 8 site that means are site that begin to degradation proven by finding of Simuliidae.